Gapit: Jaringan Mobilisasi Suara di Pilkades - Tawakkal, George Towar Ikbal (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
Villagers have practiced democracy since colonial era. They have lurah election. Government still keep it, although national politics got some regim change. Now, it is called as Village head election (Pilkades). Pilkades has a distinctive character than other election form in Indonesia. No political party in Pilkades. That asked candidates to build political machine for mobilizing voters. This article talk about how the political machine was built, what shape of the political machine is, and how it work. I conducted observation and some interviews to peoples who involved in 2016 Mranggen Village Head Election. The result, Mranggen villagers call the political machine as gapit. Gapit was constructed by prestige, social relationship, and material. Their consolidation can be distinguished in two process, transformating and creating. Gapit is a network, which has structure with three level; coordinator gapit, RW gapit, and RT gapit. They have tasks: mapping voter, developing issue, organizing meeting, distributing goods, and monitoring presence of voters in polling station. This article will contribute to discussing about extending meaning of vote broker, not only as intermediary between candidate and voters in distributing money.